Quantification of Fetal Renal Function Using Fetal Urine Production Rate and Its Reflection on the Amniotic and Fetal Creatinine Levels During Pregnancy - Ezuruike, Udoamaka; Blenkinsop, Alexander; Pansari, Amita; Abduljalil, Khaled (Frontiers in Pediatrics, 2022)
Adequate prediction of fetal exposure of drugs excreted by the kidney requires the incorporation of time-varying renal function parameters into a pharmacokinetic model. Published data on measurements of fetal urinary production rate (FUPR) and creatinine at various gestational ages were collected and integrated for prediction of the fetal glomerular filtration rate (GFR) The predicted GFR values were then compared to neonatal values recorded at birth.Collected data for FUPR across different gestational ages using both 3D (N=517) and 2D (N=845) ultrasound methods showed that 2D techniques yield significantly lower estimates of FUPR than 3D (p < 0.0001). A power law function was shown to best capture the change in FUPR with fetal age (FA) for both 2D (〖FUPR〗_2D (mL/min)=0.000169 〖 FA〗^2.19); and 3D (〖FUPR〗_3D (mL/min)= 3.21×10^(-7) 〖FA〗^4.21) data.The predicted FUPR based on the observed 3D data was shown to be strongly linearly related (R2 = 0.95) to measured values of amniotic creatinine concentration (N=664). The FUPR3D data together with creatinine levels in the fetal urine and serum resulted in median predicted fetal GFR values of 0.47, 1.2, 2.5, and 4.9 mL/min at 23, 28, 33, and 38 weeks of fetal age (50% CV) respectively. These values are in good agreement with neonatal values observed immediately at birth. The derived FUPR and creatinine functions can be utilised to assess fetal renal maturation and predict fetal renal clearance.